2008
DOI: 10.1111/j.1469-8137.2008.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Capacities and constraints of amino acid utilization in Arabidopsis

Abstract: Various amino acids, including both L- and D-enantiomers, may be present in soils, and recent studies have indicated that plants may access such nitrogen (N) forms. Here, the capacity of Arabidopsis to utilize different L- and D-amino acids is investigated and the constraints on this process are explored. Mutants defective in the lysine histidine transporter 1 (LHT1) and transgenic plants overexpressing LHT1 as well as plants expressing D-amino acid-metabolizing enzymes, were used in studies of uptake and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 64 publications
9
140
0
Order By: Relevance
“…This amino acid therefore can even shape root morphology: in plants overexpressing or lacking the Lys-transporting amino acid transporter CATIONIC AMINO ACID TRANSPORTER1 (CAT1), the lateral root density was increased by Lys and affected in the mutants. 5 The inhibitory effects of Asp-derived AAs are largely consistent with the results from Arabidopsis seedlings at higher basal N supply, 6,7 and these are at least partially physiologically explained by the complex feedback inhibition that these AAs impose on the primary biosynthesis of essential amino acids. Lysine is an essential amino acid for human nutrition, which is generally low in cereal diets.…”
Section: Low Levels Of Asp-derived Amino Acids and Their Impact On Plsupporting
confidence: 74%
“…This amino acid therefore can even shape root morphology: in plants overexpressing or lacking the Lys-transporting amino acid transporter CATIONIC AMINO ACID TRANSPORTER1 (CAT1), the lateral root density was increased by Lys and affected in the mutants. 5 The inhibitory effects of Asp-derived AAs are largely consistent with the results from Arabidopsis seedlings at higher basal N supply, 6,7 and these are at least partially physiologically explained by the complex feedback inhibition that these AAs impose on the primary biosynthesis of essential amino acids. Lysine is an essential amino acid for human nutrition, which is generally low in cereal diets.…”
Section: Low Levels Of Asp-derived Amino Acids and Their Impact On Plsupporting
confidence: 74%
“…For Picea glauca, four times higher fresh weight increase on initiation medium was observed when L-glutamine was the sole source of nitrogen compared to growth on ammonium nitrate [30]. The increase in proliferation rates observed in media containing NO 3 in addition to Gln could be due to the release of additional L-glutamine from metabolized nitrate, or by nitrate functioning as a growth promoting signal [31].…”
Section: Morphological and Developmental Characterization And Nitrogmentioning
confidence: 97%
“…Although LHT1 was previously reported to be a broad-spectrum amino acid transporter (Hirner et al, 2006;Svennerstam et al, 2007;Forsum et al, 2008), these abundant amino acids are possibly the main physiological substrates of LHT1. Growth assays on D-amino acids as the sole nitrogen source showed that the root growth of the lht1 mutant was less sensitive to the toxic D-Gln and D-Asn, suggesting that Gln and Asn are preferred substrates of LHT1.…”
Section: The Plant Defense Response Appears To Be Suppressed By Glnmentioning
confidence: 99%
“…In view of these contradictory results, we adapted an assay that uses D-enantiomeric amino acids (Erikson et al, 2004). D-enantiomers are generally toxic to plant cells but are thought to be taken up by the same transporters and with similar kinetics as their L-form counterparts (Erikson et al, 2004;Svennerstam et al, 2007;Forsum et al, 2008). Our results showed that, although both lht1 and wild-type seeds germinated well on complete Murashige and Skoog (MS) medium supplemented with a range of concentrations of D-amino acids, except for D-Cys, significant inhibition of root and leaf development were observed, indicating that all tested D-enantiomers are toxic to Arabidopsis (see Supplemental Figure 9 online).…”
Section: Gln Is One Of the Main Physiological Substrates Of Lht1mentioning
confidence: 99%